Impact of TMPRSS2-ERG fusion gene on prostate cancer cell response to chemotherapy, radiotherapy and androgen deprivation therapy - Ovtcharov, S (2015)
Many aspects of the mechanisms by which prostate cancer (PCa) progresses from being a confined tumour to advanced metastatic and castration-resistant disease remain unclear. The aim of this study is to evaluate in vitro the potential role of the fusion gene TMPRSS2-ERG in the response of PCa cells to ionising radiation (IR) and androgen deprivation therapy (ADT). This research focused on assessing the presence of the TMPRSS2-ERG transcript across various PCa cell lines and identifying any correlation between the TMPRSS2-ERG transcript and other genes, particularly genes related to DNA damage repair pathways. Several genes involved in cell metabolism and development were found to correlate with TMPRSS2-ERG but not genes involved in DNA repair. In accordance with previous reports, this research confirmed a proliferative advantage for cells expressing ERG. However this project also tested the role of ERG-status in response to chemotherapy, radiation and ADT. The data showed that VCaP and DuCaP cells exposed to low-dose radiation demonstrated decreased viability irrespective of their ERG-status. Similarly ADT decreased the viability of VCaP cells and seemed to neutralise the proliferative advantage of TMPRSS2-ERG positive cells. Stimulation with dihydrotestosterone caused increased radioresistance of TMPRSS2-ERG positive cells. Treatment with taxanes showed stronger effect on cells with lower ERG expression. This work suggests that the proliferative advantage conferred by ERG overexpression in in vitro models can be neutralised by castration and IR.